Advergaming: An Advertising Technique to Integrate Deaf People into the Gaming World - Cortez-Tuesta, María Fernanda (2024)
Advergaming, one of the innovative advertising techniques, has the potential to creatively convey brand messages to the audience. In Peru, there is a gap in integrating deaf individuals into the advertising discourse of brands and campaigns, especially when utilizing advergaming to establish a strong connection with them. This study aims to fill this gap by analyzing how the Pilsen brand, through advergaming, has contributed to creating inclusive spaces. The study also seeks to determine which elements of the advertising technique are relevant for integrating the deaf community into the gaming world. To gain a comprehensive understanding, a qualitative methodology was adopted to analyze the E-nterpreters ad, and semi-structured interviews were conducted with 12 special education students in the tenth semester at a private university in Lima. The findings revealed that Pilsen’s advergaming technique has indeed contributed to creating inclusive spaces.